Tribe of mentors short life advice from the best in the world - Timothy Ferriss (Boston Houghton Mifflin Harcourt, 2017)
We All Need Mentors. Here Are More than 100 of the World's Best. When facing life's questions, who do you turn to for advice? We all need mentors, particularly when the odds seem stacked against us. To find his own, four-time #1 best-selling author Tim Ferriss tracked down more than 100 eclectic experts to help him, and you, navigate life. Through short, action-packed profiles, he shares their secrets for success, happiness, meaning, and more. No matter the challenge or opportunity, something in these pages can help. You will learn: The three books legendary investor Ray Dalio recommends most often Lessons and tips from elite athletes like Maria Sharapova, Kelly Slater, Dara Torres, Tony Hawk, Dan Gable, and more How and why Facebook co-founder Dustin Moskovitz says no to most incoming requests The mental models of poker phenoms Daniel Negreanu, Annie Duke, Fedor Holz, and Liv Boeree The meditation and mindfulness practices of David Lynch, Jimmy Fallon, Sharon Salzberg, Rick Rubin, Richa Chadha, Sarah Elizabeth Lewis, and others The high-school loss that motivated actor Terry Crews for life. and how you can use the lesson Why TED curator Chris Anderson thinks "pursue your passion" is terrible advice Why renowned designer Debbie Millman believes in therapy but not in work-life balance How Yuval Noah Harari's Sapiens went from repeated rejections to global mega-bestseller The new beliefs, behaviors, and habits that have most helped cryptocurrency icons (founders of Ethereum, Zcash, etc.) in the last five years Why Arianna Huffington recommends that you regularly scramble apps on your phone The "bar complex" exercise that keeps country star Tim McGraw young Why bestselling author Steven Pressfield believes college students should drive trucks and become cowboys Why comedian Patton Oswalt wishes at least one catastrophic failure on anyone in the arts Astrophysicist Janna Levin's unique reframe that helps her see obstacles as opportunities Why actor Ben Stiller likes to dunk his head in a bucket of ice in the morning Why Dropbox co-founder Drew Houston's cheat sheet for his younger self would include a tennis ball, a circle, and the number 30,000. Other mentors include Neil Gaiman, Ashton Kutcher, Dita Von Teese, Marc Benioff, Evan Williams, Brandon Stanton, Esther Perel, Darren Aronofsky, Steve Aoki, Joseph Gordon-Levitt, Stephanie McMahon, Craig Newmark, Gretchen Rubin, Bear Grylls, Laura Walker, Mr. Money Mustache (Pete Adeney), Linda Rottenberg, Jesse Williams, and many more"-- Provided by publisher.
Includes index.
Keywords: Success